2021
DOI: 10.1029/2020ms002412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Coupled Modeling Approach for the Investigation of the Effects of SST Mesoscale Variability on the Atmosphere

Abstract: The large scale response in an uncoupled atmospheric simulation is the response 10 of the model rather than that of the atmosphere. 11• A coupled modeling approach is necessary to investigate the large scale atmospheric 12 response to mesoscale SST variability. 13• A pair of estimates of the oceanic heat fluxes that includes no large scale differ-14 ences is critical to produce a realistic large scale atmospheric response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The variability of the North Pacific jet exerts crucial influences on weather and climate of North America associated with the Pacific–North American pattern, synoptic features and the structure and evolution of the large‐scale circulation (Griffin & Martin, 2017; Jaffe et al., 2011; Otkin & Martin, 2004; Yu et al., 2021). Previous studies have shown that by enhancing the simulation capabilities of ocean eddies in numerical models, the forecast of extratropical cyclones and storm systems over the North Pacific in winter can be improved (Ma, Chang et al., 2015; Ma et al., 2017; Szunyogh et al., 2021), but the specific mechanism remains to be revealed. From the review, in the mid‐latitude North Pacific Ocean, there are complex phenomena of multi‐scale SST anomalies, such as the basin‐scale PDO‐pattern SST anomaly, the frontal‐scale smoothed SST with STFZ intensity anomalies, and the eddy‐scale SST anomalies with the spatial distribution of oceanic eddies.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the North Pacific jet exerts crucial influences on weather and climate of North America associated with the Pacific–North American pattern, synoptic features and the structure and evolution of the large‐scale circulation (Griffin & Martin, 2017; Jaffe et al., 2011; Otkin & Martin, 2004; Yu et al., 2021). Previous studies have shown that by enhancing the simulation capabilities of ocean eddies in numerical models, the forecast of extratropical cyclones and storm systems over the North Pacific in winter can be improved (Ma, Chang et al., 2015; Ma et al., 2017; Szunyogh et al., 2021), but the specific mechanism remains to be revealed. From the review, in the mid‐latitude North Pacific Ocean, there are complex phenomena of multi‐scale SST anomalies, such as the basin‐scale PDO‐pattern SST anomaly, the frontal‐scale smoothed SST with STFZ intensity anomalies, and the eddy‐scale SST anomalies with the spatial distribution of oceanic eddies.…”
Section: Introductionmentioning
confidence: 99%
“…Some found linear baroclinic response with a sea surface low downstream of the warm SST anomaly (Yulaeva et al 2001;Sutton and Mathieu 2002), while others produced an equivalent barotropic high downstream of the warm SST anomaly (Liu and Wu, 2004). Previous studies have shown that by enhancing the simulation capabilities of ocean eddies in numerical models, the forecast of extratropical cyclones and storm systems over the North Pacific in winter can be improved (Ma et al, 2015(Ma et al, , 2017Szunyogh et al, 2021), but the specific mechanism remains to be revealed. From the review, in the mid-latitude North Pacific Ocean, there are complex phenomena of multi-scale SST anomalies, such as the basin-scale PDO-pattern SST anomaly, the frontal-scale smoothed SST with STFZ intensity anomalies, and the eddy-scale SST anomalies with the spatial distribution of oceanic eddies.…”
mentioning
confidence: 99%